Preschool Teachers’ Attitudes towards Inclusive Education: A Survey in Indonesia and Taiwan - Wu Chi Cheng; Salim Herli; Chang Ching Yun; Chano Jiraporn (Journal of Educational Issues, 2024)
The study measures the attitudes of preschool teachers towards inclusive education in Taiwan and Indonesia with the Scale of Preschool Teachers’ Attitudes towards Inclusion (SPTAI). A total of 637 participants (Indonesian = 233 and Taiwan = 404) participated in the survey. SPATI, developed in the study, was composed of 18 items, designated in a five-point Likert Scale with a response spanning from “strongly disagree (1)” to “strongly agree (5)”. Four factors were extracted from SPTAI via exploratory factor analysis which explained 62.56% of the variance. Cronbach’s alpha for the overall scale was .93 and coefficients for the four factors were .83, .84, .82, and .70, respectively. Overall, the average scores of SPATI in Indonesia and Taiwan were 3.65 and 3.20, which exceeded the mid-point of 3.0; and the difference between the two countries was statistically significant (t = 10.98, p < .001). Results indicated that the preschool teachers in Indonesia stood between “neutral” and “somewhat agree” with leaning towards the latter. The “Taiwan preschool teachers upheld positive attitudes of inclusive education but yet their stance was more “neutral”. Significantly, Indonesian teachers were even more favourable to inclusive education than their Taiwanese counterparts. Several reasons that might explain the difference between these two countries are discussed in the study.